A teoria da asserção como método de investigação das condições da ação in statu assertionis - Pucci, Alexandre Branco (2023)
Starting from the subsistence of the conditions of the action as an autonomous legal category in the CPC/2015, the present master’s thesis has as its central theme the study of the theory of assertion as a method of investigation of the conditions of action in status assertionis. The purpose of the work was to update and contextualize the conditions of the action, through the legal debate, within the reality evidenced by the novel civil procedure diploma. Given the premise that the conditions of the action must be investigated, exclusively, in the light of the hypothesis narrated by the plaintiff in the initial petition (in favor of the reasonable duration of the process and procedural promptness), as well as that the interest and legitimacy can populate the material object of the process with the deepening of cognition (in order to guarantee the primacy of the judgment of the merits and procedural effectiveness),the intention was to demonstrate the correctness and coherence of the della prospettazione theory, to the detriment of the theory of presentation, as a technique for observing the conditions of action in the universe of eclectic theory of action